Personality traits and decision-making styles among Swedish obstetricians and gynaecologists - Raoust, Gabriel (Lund University, 2022)
The purpose of the research was to: I) compare the personality traits of obstetricians and gynecologists with those of the general population and II) examine the relationship between obstetricians' and gynecologists’ personality traits, cognitive ability, clinical experience, sex and three decision-making styles (Individual, Team and Flow) during obstetric emergencies

The data sheet is comprised of the answers (n = 472, corresponding to a 22% answering rate) to an online questionnaire that was sent out to obstetricians and gynaecologists, members of the Swedish Society for Obstetrics and Gynaecology. The questionnaire included a simplified version of the Five Factor Model questionnaire (IPIP-NEO-30), a spatial ability test (ICAR) and 15 general questions about decision-making during obstetric emergencies relating to three decision-making styles (Individual, Team and Flow).

The dataset is comprised of the answers (n = 472) to the questions in the attached questionnaire: items 1 to 24. The Likert scale was used for most questions, some others had a yes or no type of answer or multiple choice, and a few had a field for free text answering. The answers to question 3, regarding work place location, and the free text answers to question 11, regarding 'motivation of preference', have been removed to assure strict anonymity and avoid any risk of reverse identification. The specific age of respondents 70 years old or older have also been coded to avoid any risk of reverse identification, those individuals being generally quite few in the workplace. For data access to data to specific age of individuals 70 years or older, contact the responsible researcher.

Syftet med forskningen var att: I) jämföra förlossningsläkares och gynekologers personlighetsdrag med den allmänna befolkningen och II) undersöka sambandet mellan förlossningsläkares och gynekologers personlighetsdrag, kognitiv förmåga, klinisk erfarenhet, kön och tre beslutsfattandestilar (Individuell, Team och Flow) i akuta förlossningssituationer.

Data består av svaren (n = 472, motsvarande 22 % svarsfrekvens) på en webbenkät som skickades ut till förlossningsläkare och gynekologer, medlemmar i Svenska Föreningen för Obstetrik & Gynekologi. Undersökningen inkluderade en förenklad version av femfaktormodellen (IPIP-NEO-30), ett rymdsuppfattningstest (ICAR) och 15 allmänna frågor om beslutsfattande i akuta förlossningssituationer relaterade till tre beslutsstilar (Individuell, Team och Flow).

Datauppsättningen består av svaren (n = 472) på frågorna i det bifogade frågeformuläret: "items" 1 till 24. Likertskalan användes för de flesta frågorna, några andra hade ett ja eller nej typ av svar eller flerval, och några få hade ett fält för fritext. Svaren på fråga 3, angående arbetsplats, och fritextsvaren på fråga 11, angående 'motivering av preferens', har tagits bort för att säkerställa strikt anonymitet och undvika risk för bakvägsidentifiering. Den specifika åldern för respondenter 70 år eller äldre har också kodats för att undvika risk för bakvägsidentifiering, eftersom dessa individer i allmänhet är ganska få på arbetsplatsen. För åtkomst till data gällande specifik ålder för individer 70 år eller äldre, kontakta ansvarig forskare.
Personlighetsdrag och beslutsfattandestilar hos svenska förlossningsläkare och gynekologer - Personlighetsdrag och beslutsfattande stilar hos svenska förlossningsläkare och gynekologer
Keywords: decision making; beslutsfattande; Psychology, Social; Socialpsykologi; Personality Assessment; Personlighetsbedömning; Psychological Tests; Psykologiska tester; obstetrics; obstetrik; delivery (pregnancy); förlossning; hospital births; sjukhusförlossningar; physicians; läkare; social psychology; socialpsykologi; personality traits; karaktärsdrag; Emergencies; Akuta situationer; Obstetrics; Obstetrik; Practice Patterns, Physicians'; Klinisk läkarpraxis; Physicians; Läkare; Patient Safety; Patientsäkerhet; Clinical Decision-Making; Kliniskt beslutsfattande; PSYCHOLOGY; PSYKOLOGI; Gynaecology, Obstetrics and Reproductive Medicine; Gynekologi, obstetrik och reproduktionsmedicin; Psychology (Excluding Applied Psychology); Psykologi (exklusive tillämpad psykologi)